Relationships Between Olympic Weightlifting Exercises, Peak Power of the Upper and Lower Limb, Muscle Volume and Throwing Ball Velocity in Elite Male Handball Players - Hermassi, Souhail; Delank, Karl Stefan; Fieseler, Georg; Bartels, Thomas; Chelly, Mohamed Souhaiel; Khalifa, Riadh; Laudner, Kevin; Schulze, Stephan; Schwesig, René (Sportverletzung · Sportschaden, 2019)
Background This study aimed to investigate relationships between peak power (PP) as measured by upper limb (PPUL) and lower limb (PPLL) force velocity tests, maximal upper limb force assessed by clean and jerk (1RMCJ) and snatch (1RMSE) exercises, estimates of local muscle volume and throwing ball velocity.Methods Thirty elite male handball players volunteered for the investigation (age: 20.3 ± 2.1 years; body mass: 82.5 ± 10.5 kg; height: 1.85 ± 0,07 %; body fat: 13.1 ± 2.1 %). Lower and upper limb force velocity tests were performed on appropriately modified forms of a Monark cycle ergometer with measurement of PPUL and PPLL, and the corresponding respective maximal forces (F0UL and F0LL) and velocities (V0UL and V0LL). Snatched (SN) and clean and jerk (CJ) exercises were performed to one repetition maximum (1RM). Handball throwing velocity was measured with jump shot (JS) without run-up (TW) and 3 steps shot (T3 step). Muscle volumes of the upper and lower limbs were estimated with a standard anthropometric kit.Results The 1RM CJ proved to be the most important predictor for throwing velocity. All types of throwing showed a high correlation with this parameter (JS: r = 0.75; TW: r = 0.62; T3 step: r = 0.66). The highest relation was detected between jump shot and 1RM snatch technique (r = 0.82). The PPUL muscle volume correlated highly with PPUL absolute power (r = 0.70). In contrast, we did not find any comparable relations for the lower limb (muscle volume vs. PPUL absolute power: r = 0.07).Conclusions Our results highlight the contribution of both lower and upper limbs to handball throwing velocity, suggesting the need for coaches to include upper and lower limb strength weightlifting exercises and power programs when improving the throwing velocity of handball players.
Keywords: force velocity test; weightlifting exercises; muscle volume; upper limbs; lower limbs